Determination of Properties of Trace Copper Complex Solution by β-Correction Spectrophotometry - Gao*, Hong-Wen; Sheng Ye, Gui; Tao, Mei (Asian Journal of Chemistry, 2010)
The reactions were sensitive between copper(II) and dibromo-o-carboxy-chlorophosphonazo (DBKCPA) and pH 7 and between copper(II) and o-sulfobenzeneazo rhodanine (SBAR) at pH 9.5 in the presence of cetyl trimethylammonium bromide (CTMAB). Because of the serious interference of excess ligand the determination of properties of Cu complex solutions was carried out by β-correction theory instead of the single wavelength method. This investigation gave the simple determination of the complex ratio, stepwise real molar absorptivity (ε) and stepwise or cumulative stability constant (K).